The combination of amoxicillin-clavulanic acid and ketoconazole in the treatment of Madurella mycetomatis eumycetoma and Staphylococcus aureus co-infection. - Najwa A Mhmoud; Ahmed Hassan Fahal; El Sheikh Mahgoub; Wendy W J van de Sande (Public Library of Science (PLoS), 2014)
Eumycetoma is a chronic progressive disabling and destructive inflammatory disease which is commonly caused by the fungus Madurella mycetomatis. It is characterized by the formation of multiple discharging sinuses. It is usually treated by antifungal agents but it is assumed that the therapeutic efficiency of these agents is reduced by the co-existence of Staphylococcus aureus co-infection developing in these sinuses. This prospective study was conducted to investigate the safety, efficacy and clinical outcome of combined antibiotic and antifungal therapy in eumycetoma patients with superimposed Staphylococcus aureus infection. The study enrolled 337 patients with confirmed M. mycetomatis eumycetoma and S. aureus co-infection. Patients were allocated into three groups; 142 patients received amoxicillin-clavulanic acid and ketoconazole, 93 patients received ciprofloxacin and ketoconazole and 102 patients received ketoconazole only. The study showed that, patients who received amoxicillin-clavulanic acid and ketoconazole treatment had an overall better clinical outcome compared to those who had combined ciprofloxacin and ketoconazole or to those who received ketoconazole only. In this study, 60.6% of the combined amoxicillin-clavulanic acid/ketoconazole group showed complete or partial clinical response to treatment compared to 30.1% in the ciprofloxacin/ketoconazole group and 36.3% in the ketoconazole only group. The study also showed that 64.5% of the patients in the ciprofloxacin/ketoconazole group and 59.8% in the ketoconazole only group had progressive disease and poor outcome. This study showed that the combination of amoxicillin-clavulanic acid and ketoconazole treatment is safe and offers good clinical outcome and it is therefore recommended to treat eumycetoma patients with Staphylococcus aureus co-infection.